Associations Between Multiple Dimensions of Sleep and Mood During Early Adolescence: A Longitudinal Daily Diary Study. - Xie, Mingjun; Zhang, Youchuan; Wang, Wei; Chen, Huimin; Lin, Danhua (Journal of Youth & Adolescence, 2024)
Prior research has observed reciprocal associations between sleep and mood. However, these findings are primarily based on the examination of one or two aspects of sleep behaviors (e.g., duration, quality), neglecting how multiple dimensions of sleep (particularly indicators pertinent to adolescence, e.g., sleep variability) are linked to adolescent mood both daily and longitudinally. Drawing on a multidimensional framework for sleep, this study addressed the knowledge gap by examining the directionality of and differential effects for associations between multiple dimensions of sleep and mood during early adolescence. Participants were 273 Chinese early adolescents (34.39% girls; M = 11.57, SD = 1.31), who filled out a pre-survey on demographics (T1) and 7-day diaries on sleep (i.e., duration, quality, disturbance, and latency) and mood (i.e., positive and negative mood). Adolescents completed another wave of diary reports 1 year later (T2). Findings revealed both bidirectional and unidirectional, within-person effects depending on specific sleep parameters, suggesting differential associations between multiple dimensions of sleep and mood. Specifically, on days when adolescents had longer sleep latency and greater disturbance than usual, they reported higher negative mood the next day, whereas higher negative mood was linked to poorer sleep quality the next day. The longitudinal investigation found that greater variability in sleep quality at T1 was associated with higher negative mood at T2. These findings underscore the importance of understanding the complex interplay between sleep and mood by examining the directionality of and differential effects for the daily and longer-term associations between multiple dimensions of sleep and mood among early adolescents.